Thermoelectric conversion efficiency in IV-VI semiconductors with reduced thermal conductivity - Akihiro Ishida; Hoang Thi Xuan Thao; Hidenari Yamamoto; Yohei Kinoshita; Mamoru Ishikiriyama (AIP Advances, 2015)
Mid-temperature thermoelectric conversion efficiencies of the IV-VI materials were calculated under the Boltzmann transport theory of carriers, taking the Seebeck, Peltier, and Thomson effects into account. The conversion efficiency was discussed with respect to the lattice thermal conductivity, keeping other parameters such as Seebeck coefficient and electrical conductivity to the same values. If room temperature lattice thermal conductivity is decreased up to 0.5W/mK, the conversion efficiency of a PbS based material becomes as high as 15% with the temperature difference of 500K between 800K and 300K.